SREBP-2 1784 G/C Genotype is Associated with Non-Alcoholic Fatty Liver Disease in North Indians. Issue 6 (21st May 2013) - Bhatt, Surya Prakash; Nigam, Priyanka; Misra, Anoop; Guleria, Randeep; Luthra, Kalpana; Vaidya, M.; Jain, S. K.; Pasha, M. A. Qadar
Abstract : Background: Genetics of non-alcoholic fatty liver (NAFLD) in Asian Indians has been inadequately investigated. This study aims to determine the association of the 1784G > C polymorphism in the SREBP-2 gene with NAFLD in Asian Indians in north India. Methods: In this study, ( n = 335); 162 obese with NAFLD, 91 obese without NAFLD and 82 non-obese without NAFLD subjects were recruited. Abdominal ultrasound, clinical profile, anthropometry, metabolic profile, serum levels of alanine aminotransferase, aspartate aminotransferase, fasting insulin and high sensitivity C-reactive protein (hs-CRP) were analysed. Polymerase chain reaction and restriction fragment length polymorphism were used to identify individual genotypes, and the association of this polymorphism with clinical and biochemical parameters was assessed. Results: The observed frequency of G allele was 0.73 and C allele was 0.27. Frequency of C/C genotype was higher in NAFLD as compared to obese and non-obese subjects ( p = 0.003). In NAFLD subjects 57.4% were G/G homozygous, 31.5% G/C heterozygous and 11.1% were C/C homozygous. The SREBP-2 genotype frequencies deviated from the Hardy Weinberg Equilibrium ( X 2 = 6.39, p = 0.0114 ). Mean values of TG ( p = 0.002), TC ( p = 0.002), ALT ( p = 0.04) and AST ( p =0.03) levels were significantly higher in NAFLD subjects with G/C genotype as compared to G/G genotypes in obese and non-obese groups. Fasting insulin ( p = 0.03), HOMA ( p = 0.009) and hs-CRP levels were significantly higher in NAFLD subjects with G/C genotype as compared to obese and non obese subjects with G/G genotypes. Conclusion: In this study, conducted for the first time in Asian Indians, SREBP-2 1784 G > C genotype was associated with NAFLD.